2018
DOI: 10.1177/1369433218789556
|View full text |Cite
|
Sign up to set email alerts
|

Model updating–based damage detection of a concrete beam utilizing experimental damped frequency response functions

Abstract: This article evaluates the use of experimental frequency response functions for damage detection and quantification of a concrete beam with the help of model updating theory. The approach is formulated as an optimization problem that intends to adjust the analytical frequency response functions from a benchmark finite element model to match with the experimental frequency response functions from the damaged structure. Neither model expansion nor reduction is needed because the individual analytical frequency r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Another damping assumption, hysteretic damping, can more accurately describe the energy dissipation. Although it is difficult to translate the hysteretic damping mechanism into the time domain, it is promising to use the hysteretic damping assumption in the frequency domain (Pu et al [2019]).…”
Section: Damping-based Methodsmentioning
confidence: 99%
“…Another damping assumption, hysteretic damping, can more accurately describe the energy dissipation. Although it is difficult to translate the hysteretic damping mechanism into the time domain, it is promising to use the hysteretic damping assumption in the frequency domain (Pu et al [2019]).…”
Section: Damping-based Methodsmentioning
confidence: 99%
“…ey concluded that the method based on Continuous Wavelet Transform (CWT) is much more efficient than uncovering the highfrequency spikes of the structural response obtained by Hilbert-Huang transform, high-pass filtering, or Discrete Wavelet Transform (DWT). Pu et al [15] presented the use of Frequency Response Functions (FRFs) along with the model updating theory for identifying the damage occurred in concrete beams. ey formulated an optimization algorithm to set the analytical FRFs from a benchmark finite element model with those obtained through the experimental response.…”
Section: Structural Damage Detectionmentioning
confidence: 99%
“…First, we simulated the static test. According to the obtained static displacement data, under a concentrated force, the rates of length change of 71 elements before and after the damages occurred were calculated by Equation (15). The results obtained from the calculation without considering the noise are shown in Figures 4 and 5. for element 5 between nodes 5 and 6; and (2) simulate 20% stiffness damage for element 35 between nodes 1 and 15, and 20% stiffness damage for element 40 between nodes 7 and 19, respectively.…”
Section: Casesmentioning
confidence: 99%
“…First, we simulated the static test. According to the obtained static displacement data, under a concentrated force, the rates of length change of 71 elements before and after the damages occurred were calculated by Equation (15). The results obtained from the calculation without considering the noise are shown in Figures 4 and 5.…”
Section: Casesmentioning
confidence: 99%
See 1 more Smart Citation